The impact of vocational training on labor market outcomes in the Philippines - Paul Vandenberg; Jade Laranjo (Asian Development Bank (ADB), 2020)
The paper analyzes the labor market outcomes of graduates of post-secondary technical and vocational education and training (TVET) in the Philippines. Based on human capital theory, our guiding assumption is that investment in education is rewarded through higher wages and a greater likelihood of being employed. Using household data for 2015-2016, the results show significantly higher wages for TVET graduates relative to those who entered the job market with a secondary school education or below. However, individuals who both trained in TVET and pursued tertiary (university) education tend to have a lower wage than those with secondary school education or below. This counterintuitive result is explained by the tendency for such dual-level individuals to complete the lowest level of TVET. Another result is that TVET graduates are more likely to be employed than both those who only studied at secondary school or below and those who studied at the tertiary level. The results are generated from a linear regression model that corrects for sample selection into employment and from the use of propensity score matching which addresses selection into TVET.
Keywords: I26; J24; 330; labor market; Philippines; skills training; TVET